The medieval university and the ethos of knowledge: Franciscan friars, patristic tradition, and scholastic 'instruments' - Ana Paula Tavares Magalhães (Universidade Estadual de Maringá, 2015)
The encounter between the Christian ethos of knowledge - synthetized by Saint Augustine and largely adopted by medieval Fathers - and Aristotle's "scientific" method - based on logics and on the sensitive knowledge of Scholasticism -, is among the main accomplishments of the Latin Western world, and took place, mainly, within the University. Epistemological discussions joined institutional debates - intensified by disputes between secular groups, and mendicants, with highlight to the work of Bonaventure of Bagnoregio (c.1217-1274), minister general of the Franciscan Order and a master at the University of Paris. In his formulations on the knowledge and the statute of the Franciscan institution, Bonaventure placed himself inside the university debate, settling the bases to the Franciscan thought and to the work of his Order - both in the Church and in the University.